Fenomenologi Diri dan Konstruksi Sosial Mengenai Kebudayaan: Edmund Husserl dan Jejak-Jejaknya pada Maurice Merleau-Ponty dan Peter Berger - Budhy Munawar Rachman (ILMU USHULUDDIN, 2013)
Edmund Husserl is wellknown as a person who created his own phenomology. This article articulates Husserl’s idea which has been continued by Maurice Merleau-Ponty in human affair, and by Peter Berger in the matter of social construction. Merleau-Ponty criticizes Descartes who separated between res extensa (body) and res cogitans (consciousness), and proposes a concept of human being as sspiritually-body (embodied spirit) and bodily-spiritual (spiritualized-body.) The main core of Merleau-Ponty’s philosophy is to see human being in the unity of body-soul-spirit at once, without separation. Whilst Berger views that human being actually forms his world by following tendency and development of his—apart from psychology—socio- culture. Thence culture becomes main key of Berger’s philosophy.